1997
DOI: 10.1093/oxfordjournals.molbev.a025742
|View full text |Cite
|
Sign up to set email alerts
|

Early evolution of metazoan serine/threonine and tyrosine kinases: identification of selected kinases in marine sponges

Abstract: The phylum Porifera (sponges) was the first to diverge from the common ancestor of the Metazoa. In this study, six cDNAs coding for protein-serine/threonine kinases (PS/TKs) are presented; they have been isolated from libraries obtained from the demosponges Geodia cydonium and Suberites domuncula and from the calcareous sponge Sycon raphanus. Sequence alignments of the catalytic domains revealed that two major families of PS/TK, the "conventional" (Ca(2+)-dependent) protein kinase C (PKC), the cPKC subfamily, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
83
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(84 citation statements)
references
References 25 publications
1
83
0
Order By: Relevance
“…Recent molecular biological studies have revealed that the siliceous demosponges are provided with the genetic "toolkit" to construct these skeletal elements, the spicules, functional animals being composed of differentiated cells that interact in a tissue-like manner and that allow the formation of a body plan (Müller et al 2004;Müller 2005;Pilcher 2005). M. chuni is a siliceous sponge, belonging to the phylogenetically oldest Poriferan class, the Hexactinellida (Kruse et al 1997). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent molecular biological studies have revealed that the siliceous demosponges are provided with the genetic "toolkit" to construct these skeletal elements, the spicules, functional animals being composed of differentiated cells that interact in a tissue-like manner and that allow the formation of a body plan (Müller et al 2004;Müller 2005;Pilcher 2005). M. chuni is a siliceous sponge, belonging to the phylogenetically oldest Poriferan class, the Hexactinellida (Kruse et al 1997). …”
Section: Discussionmentioning
confidence: 99%
“…Based on molecular biological (Kruse et al 1997) and geological (Reitner andestablished as the oldest, having evolved between Neoproterozoic glaciations (720-585 Ma), sometimes referred to as "snowball" Earth (for a review, see Corsetti et al 2006). During this period, a cycle of silicate weathering and carbonate precipitation, prior to or simultaneously with the glaciations, has been proposed to have resulted in the dissolution of surface rocks composed of insoluble silicates (CaSiO 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…50,51 In addition, FuGENE 6 reagent, PCR-DIG (digoxigenin)-ProbeSynthesis Kit, anti-DIG AP Fab fragments and CDP [disodium 2-chloro-5- (4-methoxyspiro{1,2-dioxetane-3,2'-(5'-chloro)-tricyclo [3.3.1.1. 3,7 ]decan}-4-yl)phenyl phosphate] from Roche Diagnostics (Mannheim; Germany); RPMI-1640 and OptiMEM from Life Technologies (Karlsruhe; Germany); geneticine G418 from Invitrogen (Groningen; The Netherlands); tributyltin and labelled anti-rabbit Ig from Sigma (Deisenhofen; Germany); AC-DEVD-AMC from Peptide Institute (Osaka; Japan); monoclonal anti-Bcl-2 [human] antibodies (mouse) from Santa Cruz (Santa Cruz, Cal; USA); anti-mouse (Cy3 labeled) and anti-rabbit (FITC-labeled) from Dianova (Hamburg; Germany); the mouse anti-Hexa-histidine monoclonal antibody (McAb-anti-His) from Invitrogen (Groningen; The Netherlands).…”
Section: Methodsmentioning
confidence: 99%
“…For the isolation of the cDNA encoding cystatin, a cDNA library of Suberites domuncula was used (Kruse et al, 1997). From this a set of 30·000 expressed sequence tag sequences has been compiled.…”
Section: Cloning Of Cystatin Cdna From S Domunculamentioning
confidence: 99%